Monotasking: Solusi Distraksi Era Modern - Sarla Nabila; Ira Qurrotul Ain; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2023)
Abstract - The aim of this study is to find out the benefits and tips for implementing monotasking in everyday life. In this study report, a descriptive qualitative method was used by taking notes because the data source was obtained by listening to the oral narrative from the Greatmind YouTube channel entitled